The Effects of Type of Instruction of English Prepositions with Varying Degrees of Salience - Ana Mónica Preciado-Sánchez; José Luis Moreno-Vega (Lenguaje)
It is still unknown if different types of input exposure are equally effective at facilitating the learning of forms that vary in their level of perceptual salience. A pretest-posttest design was implemented during four training sessions to find if university students of English as a foreign language could learn three prepositions which are used in the context of forms of transportation: in, on, and by. Eighty-three participants were assigned one of three different conditions: a) control, b) textual enhancement and c) explicit instruction. Automatized-explicit and declarative-explicit knowledge was assessed before and after the treatment. The results revealed that textual enhancement did not lead to learning of the target forms. Only explicit instruction caused a learning effect. Explicit instruction of less salient forms promoted primarily automatized-explicit knowledge and declarative-explicit knowledge of those forms whereas explicit instruction of more salient forms resulted only in declarative-explicit knowledge.